CODED LEADERSHIP; DEVELOPING SCALABLE MANAGEMENT IN AN AI-INDUCED QUANTUM WORLD - Sairam, Pinisetti Swami; K., Hemachandran; Rodriguez, Raul Villamarin (BOCA RATON : CRC PRESS, 2022)
Coded Leadership: Developing Scalable Management in an AI-induced Quantum World will assist researchers and industry experts working towards improvising their processes and developing and deploying strategies in an AI-induced world of quantum computing. The book introduces the necessary background to understand the challenges in today's organizational leadership and how artificial intelligence enables learning to be viewed from a probabilistic framework. Key Features Introduction to Quantum Natural Language Processing. Overview of Leadership and AI. The Age of Quantum Superiority. Challenges to Today's Leadership. AI-induced Strategic Implementation and Organizational Performance. This book serves as a reference for researchers that need to know how AI and quantum can assist in leadership and organizational performance. The book will also be helpful for students that want to learn more about AI and quantum computing in various business applications.
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Artificial Intelligence; COMPUTERS / Computer Science; Leadership -- Technological innovations; Artificial intelligence; Quantum computing